Peran Kepemimpinan Perawat Transformasional dalam Menerapkan Budaya Keselamatan Pasien - Ade Kiki Zakiah; Siti Aminah; Farida Murtiani; Fatimah Fatimah (Jurnal Kesehatan Komunitas, 2026)
Patient safety culture in hospitals is strongly influenced by the quality of nursing leadership, yet empirical evidence from infectious disease referral hospitals in Indonesia remains limited, particularly regarding the role of transformational head nurse leadership. This study aimed to analyze the relationship between the transformational leadership style of head nurses and the implementation of patient safety culture at Sulianti Saroso Infectious Diseases Hospital, Jakarta. This quantitative research employed a descriptive correlational design with a cross-sectional approach. Respondents were staff nurses in inpatient units selected using simple random sampling, with inclusion criteria of actively working nurses willing to participate and exclusion criteria of nurses on leave (maternity, sick, study), internship nurses, the researcher, and head nurses, resulting in 48 respondents. Data were collected using the Hospital Survey on Patient Safety Culture (HSOPS) Version 2 and a validated transformational leadership questionnaire, then analyzed using univariate and bivariate analyses with the chi-square test. Most respondents perceived the transformational leadership of head nurses as good (64.6%) and the patient safety culture as good (54.2%). There was a significant relationship between transformational leadership and patient safety culture (p = 0.004), with a Prevalence Odds Ratio (POR) of 7.944 (95% CI: 2.033–31.041), indicating that nurses who perceived transformational leadership as good had nearly eight times higher odds of reporting a good patient safety culture. These findings highlight the importance of strengthening transformational leadership development programs for ward managers as a strategy to improve patient safety culture and service quality in infectious disease referral hospitals.​